The Many and Varied Roles of Tetraspanins in Immune Cell Recruitment and Migration - Yeung, Louisa; Hickey, Michael J.; Wright, Mark D. (Frontiers in Immunology, 2018)
Immune cell recruitment and migration is central to the normal functioning of the immune system in health and disease. Numerous adhesion molecules on immune cells and the parenchymal cells they interact with are well recognised for their roles in facilitating the movements of immune cells throughout the body. A growing body of evidence now indicates that tetraspanins, proteins known for their capacity to organise partner molecules within the cell membrane, also have significant impacts on the ability of immune cells to migrate around the body. In this review, we examine the tetraspanins expressed by immune cells and endothelial cells that influence leukocyte recruitment and motility, and describe their impacts on the function of adhesion molecules and other partner molecules that modulate the movements of leukocytes. In particular, we examine the functional roles of CD9, CD37, CD63, CD81, CD82 and CD151. This reveals the diversity of the functions of the tetraspanin family in this setting, both in the nature of adhesive and migratory interactions that they regulate, and the positive or inhibitory effects mediated by the individual tetraspanin proteins.